The Effect of Geometric Configurations on the Elastic Behavior of an Edge-Cracked Bonded Strip - Xin Lan; Shaobo Ji; Nao-Aki Noda; Yong Cheng (Advances in Materials Science and Engineering)
Interface cracks often initiate around the bonding free-edge corner due to the high-stress concentration. In this research, the elastic behavior of an edge-cracked dissimilar bonded strip subjected to remote tensile load is investigated using the proportional crack tip opening displacement method based on FE analysis for arbitrary material combinations. The stress intensity factor, energy release rate, and mode mixity are computed and compared systematically with varying geometrical configurations and material combinations. Then, the combined effects of the relative height of the bonded component and material combination are discussed for the typical engineering materials.